2007
DOI: 10.1017/s1751731107283909
|View full text |Cite
|
Sign up to set email alerts
|

Pig acute-phase protein levels after stress induced by changes in the pattern of food administration

Abstract: A total of 240 pigs, 74 days old, half boars and half females, were included in a trial designed to assess the effect of the stress caused by changes in the pattern of food administration on the concentration of acute phase proteins (APP) and productive performance parameters. Half of the animals (pigs fed ad libitum, AL group) had free access to feed, while the rest were fed following a disorderly pattern (DIS group), in which animals had alternating periods of free access to feed and periods of no feeding, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 38 publications
5
45
0
Order By: Relevance
“…Apart from immune stimuli, haptoglobin can also be released in response to other stressors like hot ambient temperature (Heo et al, 2005), transport (Piñeiro et al, 2007b) or unpredictable feeding practices (Piñeiro et al, 2007a). In the present study, haptoglobin levels were unrelated to cortisol levels.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Apart from immune stimuli, haptoglobin can also be released in response to other stressors like hot ambient temperature (Heo et al, 2005), transport (Piñeiro et al, 2007b) or unpredictable feeding practices (Piñeiro et al, 2007a). In the present study, haptoglobin levels were unrelated to cortisol levels.…”
Section: Discussionmentioning
confidence: 42%
“…It is noteworthy that CBG, which is a protein of hepatic origin like positive and negative acute phase proteins, displays reduced concentrations in cases of inflammatory conditions (Garrel, 1996), and thus varies in the opposite way to haptoglobin. These opposite variations have also been observed in pigs, in inflammatory (Carroll et al, 2003) as well as in other stressful conditions (Heo et al, 2005;Piñeiro et al, 2007a and2007b).…”
Section: Discussionmentioning
confidence: 68%
“…These authors observed an increase in plasma cortisol levels in calves fed milk formula in comparison to the control group fed colostrum and milk, which may indicate that changes in the feeding system may induce stress. In addition, the effect of changes in the feeding pattern on the level of plasma APP's has been proven (Pineiro et al 2007). This may indicate that stress-induced changes, resulting in the short-term up-regulation of haptoglobin expression, can be attributed to changes in the feed, and particularly to its composition.…”
Section: Discussionmentioning
confidence: 99%
“…This may result from the higher lipid content in milk compared to the milk replacer (Hammon and Blum 1998, Kuhne et al 2000, Rauprich et al 2000 as well as from the lower digestibility of palm and coconut oil mixture (84.6%) when compared to milk fat (Huuskonen et al 2005). Carpintero et al (2005) and Pineiro et al (2007) claim that the concentration of plasma apoA-I decreased in piglets in response to stress. Thus, it may be hypothesized that a decrease in the expression of plasma apoA-I observed in the present study in calves fed milk replacer was additionaly related to stress-induced feeding changes.…”
mentioning
confidence: 99%
“…This association is questionable as sow characteristics (live births per litter and still births per litter) were not the primary targets in this investigation and therefore sow-level clustering of data was not controlled for in the analysis. However, larger litter size is a contributor of compromised pig welfare (Rutherford et al, 2013) and previous studies have demonstrated that high Hp levels are a strong indicator of decreased welfare on pig farms (Piñeiro et al, 2007a and2007b).…”
Section: Discussionmentioning
confidence: 99%